The Influence of Price, Brand Image, and Word of Mouth on Purchasing Decisions at Toksik Pinang Lombang Cafe Labuhanbatu Utara - Lestari, Junita; Pitriyani, Pitriyani; Munthe, Abdillah Menri (Amkop Management Accounting Review (AMAR), 2026)
The cafe business in the modern era is growing rapidly along with changes in people's lifestyles, making it a place for social communication and entertainment. This study aims to examine how price, brand perception, and recommendations from others influence consumer purchasing choices at Cafe Toksik Pinang Lombang, North Labuhanbatu, which has been operating since September 2021, with a turnover increasing from IDR 96 million (2021-2022) to IDR 240 million (2024-2025). Using descriptive quantitative methods, the study involved 100 respondents aged 15-40 years through purposive sampling and Likert scale questionnaires. Conducting data analysis using SPSS, looking at the validity test (r count > r table), reliability (Cronbach's Alpha > 0.60), on classical assumptions (normality sig. 0.052, VIF <10, heteroscedasticity sig. >0.05), multiple linear regression (Y = -0.128 + 0.365X1 + 0.246X2 + 0.384X3), t test (price t = 5.683 p = 0.000; brand image t = 3.301 p = 0.001; WOM t = 4.724 p = 0.000), and F test (182.050 p = 0.000). The results showed that all three variables had a significant positive influence partially and simultaneously, with R²=0.851 (85.1% of the variation in purchasing decisions). Price had the strongest influence.